Ohmic Heating Produces Stable Betacyanin Extract From Dragon Fruit Peel: Pemanasan Ohmik Menghasilkan Ekstrak Betasianin Stabil dari Kulit Buah Naga - Elena Febri Kusumawati; Syarifa Ramadhani Nurbaya (Academia Open, 2025)
General Background: Natural plant pigments are increasingly utilized as alternatives to synthetic food colorants, including betacyanin compounds. Specific Background: Red dragon fruit peel contains betacyanin and is largely underutilized, while ohmic heating offers rapid and uniform extraction technology. Knowledge Gap: Limited studies evaluate solvent variation and electrical voltage in ohmic heating extraction related to betacyanin stability under pH and storage temperature conditions. Aims: This study examines the role of solvent type and electrical voltage in extracting betacyanin from red dragon fruit peel and evaluates pigment stability based on pH and temperature storage. Results: Extraction using distilled water, NaCl 0.25%, and citric acid 0.25% with 30V–50V treatments showed no significant difference in betacyanin content at pH 5 and 7. Storage in refrigerator and incubator conditions produced similar pigment stability, although incubator storage altered lightness values. Novelty: This study combines solvent and voltage variation in ohmic heating extraction with stability testing across pH and storage conditions. Implications: The findings support red dragon fruit peel utilization as a natural pigment source and provide reference for ohmic heating extraction processes in food applications. Highlights: Variation of Extraction Liquids and Electrical Treatments Generated Comparable Pigment Content Stability Under PH Modification. Cold Storage Maintained Chromatic Properties Across Tested Treatments. Elevated Storage Temperature Altered Brightness Measurement Characteristics. Keywords: Betacyanin Pigment, Ohmic Heatin, Red Dragon Fruit Peel, Solvent Variation, Electrical Voltage